Solvent extraction of phenol from aqueous solution with benzyl 2‐ethylhexyl sulfoxide as a novel extractant. (29th July 2015) - Wang, Shixiong; Shi, Deqiang; Yang, Ruisi; Xu, Yan; Guo, Hong; Yang, Xiangjun
<x xml:space="preserve">Abstract</x> In this paper, we synthesized a novel structure of sulfoxide, benzyl 2‐ethylhexyl sulfoxide (BSO), and evaluated its performance for extracting phenol. The influences of several variables on phenol extraction were investigated, including equilibrium time, pH value, temperature, and salts in the aqueous phase. It was found the BSO dissolved in kerosene was an effective extractant for the recovery of phenol from an aqueous solution at pH = 2. The transfer mechanism of phenol into the organic phase was proved to be the solvation reaction by BSO through hydrogen bonds as a phenol: BSO 1:1 complex. The temperature variation tests showed that the extraction process is exothermic, and phenol extraction efficiency decreased with increased reaction temperature. Phenol could be efficiently stripped from the loaded organic phase with a sodium hydroxide solution. The results obtained establish that the BSO/kerosene system has potential for practical applications in the recovery of phenol from aqueous solutions.